Two seconds is all it takes: European starlings (Sturnus vulgaris) increase levels of circulating glucocorticoids after witnessing a brief raptor attack - Jones, B.; Smith, A.; Bebus, Sara; Schoech, S. (2016)
© 2015 Elsevier Inc.. Researchers typically study "acute" activation of the hypothalamic-pituitary-adrenal (HPA) axis by measuring levels of circulating glucocorticoids in animals that have been exposed to a predator or a cue from a predator (e.g., odor), or have experienced a standardized capture-and-restraint protocol, all of which are many minutes in duration. However, exposure to predators in the "wild", either as the subject of an attack or as a witness to an attack, is generally much shorter as most depredation attempts upon free-living animals last < 5 s. Yet, whether a stimulus lasting only seconds can activate the HPA axis is unknown. To determine if a stimulus of a few seconds triggers a glucocorticoid response, we measured levels of corticosterone (CORT; the primary avian glucocorticoid) in wild-caught European starlings (Sturnus vulgaris) after they witnessed a brief (< 2-8 s) raptor attack upon a conspecific, a human "attack" (i.e., a researcher handling a conspecific), and an undisturbed control. Witnesses of a raptor attack responded with CORT levels comparable to that induced by a standardized capture-and-restraint protocol. Glucocorticoid levels of individuals following the control treatment were similar to baseline levels, and those that witnessed a human "attack" had intermediate levels. Our results demonstrate that witnessing a predator attack of very brief duration triggers a profound adrenocortical stress response. Given the considerable evidence of a role for glucocorticoids in learning and memory, such a response may affect how individuals learn to recognize and appropriately react to predators.